2021
DOI: 10.1080/13504851.2021.1994518
|View full text |Cite
|
Sign up to set email alerts
|

Child penalties across industries: why job characteristics matter

Abstract: This article investigates the impact of parenthood on women's labour market outcomes in Belgium. Using administrative data and an event study design, we show that mothers lose 32% of their labour earnings relative to fathers, up to eight years after the birth of their first child. Furthermore, we find a strong positive correlation between the size of the child penalty for a given sector and the share of its workers who report working atypical work schedules or irregular hours, suggesting that job characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…While the gender gaps in the labour market have narrowed considerably in recent years, sizable ones still exist and childbearing has gradually become their main driver (Kleven et al, 2019a). For example, prior literature has shown that after childbirth mothers participate less in the labour market relative to fathers (Rosenzweig and Wolpin, 1980;Angrist and Evans, 1998;Jacobsen et al, 1999;Kleven and Landais, 2017;Kleven et al, 2019aKleven et al, ,b, 2020Sieppi and Pehkonen, 2019;Fontenay et al, 2021;Kleven et al, 2021;Nieto, 2021), are less likely to be employed (Gutiérrez-Doménech, 2005;Narayan and Smyth, 2006;Cristia, 2008;Michaud and Tatsiramos, 2011;Fitzenberger et al, 2013;Kleven, 2022) and work fewer hours (Lundberg and Rose, 2000;Bridges and Mumford, 2001;Sasser, 2005;Paull, 2008;Miller, 2011;Fernández-Kranz et al, 2013;Lundborg et al, 2017;Kleven et al, 2019aKleven et al, , 2020Fontenay et al, 2021;Kleven et al, 2021). Mothers are also less productive (Azmat and Ferrer, 2017;Krapf et al, 2017), less experienced (Klepinger et al, 1999;Fernández-Kranz et al, 2013), more likely to work in the public sector (Fernández-Kranz et al, 2013;Kleven et al, 2019a) and have lower labour responsibilities (Cools et al, 2017;Kleven et al,...…”
Section: Introductionmentioning
confidence: 99%
“…While the gender gaps in the labour market have narrowed considerably in recent years, sizable ones still exist and childbearing has gradually become their main driver (Kleven et al, 2019a). For example, prior literature has shown that after childbirth mothers participate less in the labour market relative to fathers (Rosenzweig and Wolpin, 1980;Angrist and Evans, 1998;Jacobsen et al, 1999;Kleven and Landais, 2017;Kleven et al, 2019aKleven et al, ,b, 2020Sieppi and Pehkonen, 2019;Fontenay et al, 2021;Kleven et al, 2021;Nieto, 2021), are less likely to be employed (Gutiérrez-Doménech, 2005;Narayan and Smyth, 2006;Cristia, 2008;Michaud and Tatsiramos, 2011;Fitzenberger et al, 2013;Kleven, 2022) and work fewer hours (Lundberg and Rose, 2000;Bridges and Mumford, 2001;Sasser, 2005;Paull, 2008;Miller, 2011;Fernández-Kranz et al, 2013;Lundborg et al, 2017;Kleven et al, 2019aKleven et al, , 2020Fontenay et al, 2021;Kleven et al, 2021). Mothers are also less productive (Azmat and Ferrer, 2017;Krapf et al, 2017), less experienced (Klepinger et al, 1999;Fernández-Kranz et al, 2013), more likely to work in the public sector (Fernández-Kranz et al, 2013;Kleven et al, 2019a) and have lower labour responsibilities (Cools et al, 2017;Kleven et al,...…”
Section: Introductionmentioning
confidence: 99%